2022
DOI: 10.1186/s12887-022-03405-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of extrauterine growth restriction in very preterm infants with bronchopulmonary dysplasia: a multi-center study in China

Abstract: Objective Nutritional deficiency soon after birth is a risk factor of chronic lung disease (bronchopulmonary dysplasia, BPD). Afflicted infants are further prone to inadequate growth during hospitalization (extrauterine growth restriction, EUGR). This multi-center retrospective study investigated risk factors of EUGR, specifically in very preterm infants with BPD. Method Data of infants with BPD who were born less than 32 weeks gestation (n = 1010)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Therefore, these factors’ high SHAP values emphasize their importance in predicting growth outcomes. In the weight baseline dataset, GA displayed a positive correlation, suggesting that lower gestational age at birth, a common risk factor for EUGR, is linked with growth restriction ( 78 , 79 ). However, in the weight follow-up dataset, GA was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these factors’ high SHAP values emphasize their importance in predicting growth outcomes. In the weight baseline dataset, GA displayed a positive correlation, suggesting that lower gestational age at birth, a common risk factor for EUGR, is linked with growth restriction ( 78 , 79 ). However, in the weight follow-up dataset, GA was negatively correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Infants with BPD require increased energy to support their respiratory muscle workload, however, fluid restriction may result in inadequate energy intake leading to EUGR, which can impede lung and pulmonary vessel development and repair. The risk of EUGR is positively associated with the severity of BPD in preterm infants [ 20 ]. Our study revealed that EUGR at 36 weeks’ PMA was associated with poor long-term prognosis, emphasizing the importance of strengthening perinatal and enteral nutrition management after birth to prevent long-term adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Infants with early or developing BPD should be fed with human milk, preferably with fortified fresh maternal milk 68 . Ideally, infants with BPD should receive a fluid intake of no more than 135-150 ml/kg/day and an energy intake of 120-150 kcal/kg/day 96,97 . Providing high energy in a low volume remains a challenge and is the main cause of growth restriction in these infants.…”
Section: Nutritional Strategiesmentioning
confidence: 99%
“…Specialized nutritional strategies may be needed to overcome difficulties that are common in BPD infants, such as gastroesophageal reflux and poorly coordinated feeding 96 . Table 4 summarizes a practical nutritional approach to use in infants at risk of, or with, BPD 96,97 .…”
Section: Nutritional Strategiesmentioning
confidence: 99%
See 1 more Smart Citation